A multiplex PCR‐based technique for identification of Biscogniauxia mediterranea and Obolarina persica causing charcoal disease of oak trees in Zagros forests. Issue 3 (10th March 2017) - Safaee, D.; Khodaparast, S. A.; Mirabolfathy, M.; Mousanejad, S.
Summary: Zagros oak ( Quercus spp.) forests (ZOF) cover approximately 4 million hectares of the Zagros Mountains in Iran. Oak charcoal disease caused by Biscogniauxia mediterranea and Obolarina persica has recently increased in some regions of ZOF. Detection of these fungi in host tissue and identification of the anamorphs by traditional methods have limitations and difficulties which were overcome using two primers, OP1 and OP2, based on rDNA sequences of O. persica and used along with the specific primers MED1 and MED2 for B. mediterranea to develop a multiplex PCR. This method was used to correctly identify 1 pg of fungal DNA per 1 mg of inner bark tissues of Quercus brantii, Q. infectoria and Q. libani .